How does nutrient and sediment loading affect estuarine ecosystem. - Yahya, Khairun (Universiti Sains Malaysia, 2016)
The Pinang River estuary is classified as a microtidal, primary and partly-mixed system where approximately 6.5 km of the estuary experiences tidal intrusion from the mouth up to its middle zone. Results from bathymetry and hydrodynamic studies indicate that, Pinang River is a shallow river, with a depth of 0.18-2.10 m (at low tide) and 0.41-3.03 m (at high tide) .. During the lowest spring tide, the width of the river is about 5.9-80.0 m widen to 5.9-121.0 m during the highest level of spring tide. At the freshwater part, the river depth is between 0.29-1 .68 m while the river width varies between 1.8-2.4 m. The river discharge was high (6 .12 m3/s) during ebb tide. Pinang River has a long residence time within 2 to 3 days.